The journey south - Wortham, Reavis Z. (Wortham, Reavis Z. Cap Whitlatch, 2024)
"Texas cowboy Cap Whitlatch has never shied away from hard work. Whether driving cattle or busting broncos, he gets the job done right. When he hires on with a ranch, he earns his pay with blood and sweat, keeping him honest. And when a friend is in dire need, Cap will move the tallest mountains to defend and protect them from harm. Gil Vanderburg has known Cap since they were children. Now, he's in jail for murder in a small Oklahoma town. To see justice served right, Cap volunteers to escort his friend to South Texas where he will stand trial for robbery. But they're not quite traveling alone along the unhealthy trail in Indian territory. Three bloodthirsty Cherokee brothers want revenge on Gill for killing their sibling. A pair of vicious outlaws are after the gold in Cap's saddlebags. And the marshal pursuing them all is determined to bring every lawbreaker in--dead or alive. Cap is not about to let any man--no matter which side of the law he falls on--deter him from fulfilling his righteous mission. And he will show no mercy to anyone who tries..."--